Exploring the Value of Radiomics Features Based on B-Mode and Contrast-Enhanced Ultrasound in Discriminating the Nature of Thyroid Nodules - Guo, Shi Yan; Zhou, Ping; Zhang, Yan; Jiang, Li Qing; Zhao, Yong Feng (Frontiers in Oncology, 2021)
Background: As the improvement of the ultrasound imaging resolution and the application of various new technologies, The detection rate of thyroid nodules has increased greatly in recent years. However, there are still challenges in accurately diagnosing the nature of the thyroid nodules. The study aimed to evaluate the clinical application value of the radiomics features which extracted from B-mode Ultrasound (B-US) images combined Contrast-Enhanced Ultrasound (CEUS) images in the differentiation of benign and malignant thyroid nodules by comparing the diagnostic performance of four logistic models. Methods: We retrospectively collected and ultimately included B-US images and CEUS images of 98 nodules from 98 patients, and then extracted the corresponding radiomics features from these images respectively. Meanwhile, a senior radiologist combined the thyroid imaging reporting and data system (TI-RADS) and the enhancement pattern of the ultrasonography to make a graded diagnosis of the malignancy of these nodules. Next, based on these radiomics features and grades, logistic regression was used to help building the models (B-US radiomics model, CEUS radiomics model, B-US+CEUS radiomics model and TI-RADS+CEUS model). Finally, the study assessed the diagnostic performance of these radiomics features with a comparison of the area under curve (AUC) of the receiver operating characteristic curve of four logistic models for predicting the benignity or malignancy of thyroid nodules. Results：The AUC in the differential diagnosis of the nature of thyroid nodules was 0.837 for B-US radiomics model, 0.837 for CEUS radiomics model, 0.945 for B-US+CEUS radiomics model and 0.838 for TI-RADS+CEUS model respectively. Compare to the TI-RADS+CEUS model, there were no statistical significance was observed in AUC between B-US radiomics model, CEUS radiomics model and TI-RADS+CEUS model (P>0.05). However, a significant difference was observed between B-US+CEUS radiomics model and others(P<0.05). Conclusion：Compared with TI-RADS+CEUS model, both B-US radiomics model and CEUS radiomics model demonstrated similar performance in diagnosing the benignity or malignancy of thyroid nodules, while B-US+CEUS radiomics model showed a remarkable advantage over the others. It was proved that B-US radiomics features and CEUS radiomics features are of high clinical value as the combination of the two have better diagnostic performance.